Historical changes in nutrient inputs from humans and anadromous fishes in New England's coastal watersheds - Cornelia W. Twining; Derek C. West; David M. Post (Limnology and Oceanography, 2013)
Prior to Euro‐American contact, anadromous alewives ( Alosa pseudoharengus ) were abundant throughout eastern North America. In the 400 yr since Euro‐American settlement began in the region, anadromous alewife populations have declined by an order of magnitude or more while human land use has simultaneously intensified. Here we asked how lake nutrient inputs in the southern New England region have changed over the past 400 yr by examining nutrient inputs to four lakes in coastal Connecticut that differ in their land‐use history and their history of accessibility to anadromous alewife. We estimated the flux of nitrogen and phosphorus from both anadromous alewife and the landscape and conducted a paleoecological analysis of stable isotopes ( δ 15 N, total δ 13 C, organic δ 13 C) and nutrients (N : P, C : N, organic C) from lake sediment cores in each of our study watersheds. Nutrient loading models suggest that allochthonous nutrient inputs are now dominated by watershed land use and our paleoecological data also reflect major changes in human land use. Loading models also suggest that prior to Euro‐American contact, anadromous alewife runs historically provided up to 95% of allochthonous phosphorus inputs and up to 68% of allochthonous nitrogen inputs to the region's coastal lakes. However, paleoecological data suggest that even the large nutrient inputs from abundant past alewife populations may never have had the same long‐term effect on lake nutrient dynamics as those from the landscape due to the unique combination of the alewife's life history and coastal Connecticut's climate and geomorphology.